Diagnosis and management of small renal masses: the new PSA?. Issue 5 (1st October 2013) - Joji, Nikita; Challacombe, Ben
Abstract The authors provide an overview of recent management modalities for small renal masses and highlight the role of developing diagnostic tools such as percutaneous renal biopsy. Copyright © 2013 John Wiley & Sons